(untitled) (Journal of Engineering, 2006)
This paper includes study of performance of single cylinder, 4-stroke spark ignition engine Ricardo E6, with variable compression ratio, spark timing and equivalence ratio, fueled with supplementary hydrogen to gasoline. The speed of 25 rps and higher useful compression ratio were chosen in studying the effect of wide range of equivalence ratios and spark timing. The results showed that HUCR for mixture of two fuels was (9:1). The brake power when operated with gasoline was higher than when it was fueled with hydrogen alone, but when mixing two fuels the brake power increased and became higher than that when working with gasoline to a certain limit (the hydrogen volumetric ratio in the mixture reached 80%), after this limit the brake power reduced by increasing hydrogen volumetric ratio. The equivalence ratio at which the brake power reach its highest value was between (Ø=1-1.1) when mixing the two fuels. The results showed that the engine can work with very lean equivalence ratios with supplementary hydrogen, the indicated thermal efficiency increased also, and the brake specific fuel consumption reduced when hydrogen volumetric ratio increased.